Preparation of Ni - Based Ag - Cu Alloy Electrode and Its Application in Degradation Process of Salicylic Acid - SONG Xiu - li, YAN Rui - jing, LIU Xian, LU Bao - ping (Cailiao Baohu, 2021)
In order to provide a theoretical basis for the preparation of electrode and the degradation of salicylic acid Ni - based Ag - Cu alloy electrodes were prepared by electrodeposition method, which was further applied in the degradation process of salicylic acid. The electrochemical properties of the Ni - based Ag - Cu alloy electrodes with different molar ratios of Ag - Cu were studied. Under the same plate spacing, plus voltage, electrolysis time, the effects of electrolyte concentration on the degradation rate of salicylic acid were explored and the electrochemical oxidation degradation and ultrasound - assisted electrochemical synergetic degradation rate were compared. Results showed that under the same temperature, current density, electrode materials and distance between the anode and the cathode, when nAg∶nCu in the electrodeposition solution was equal to 8∶2, the surface morphology of Ni - based Ag - Cu alloy electrode is good, and the degradation rate of salicylic acid was the highest. The most suitable Na2SO4 electrolyte concentration was 1.064 g/L. Under this condition, the degradation rate of salicylic acid was 98.01%, and the ultrasound - assisted electrochemical oxidation rate was 99.89%, indicating that the degradation rate of salicylic acid under the synergy effect was higher.